- Strategic challenges to Iraqi national security after 2023. Lecturer - Lecturer, Dr. Youssef Radi Kazem; Assistant Lecturer, Abdul-Jabbar Karim Abdul-Amir (The college of law and political science journal, 2023)
The study of security as a main axis is an attempt by us to establish mechanisms to work according to standards commensurate with the security reality in which Iraq is living and centered on preserving the entity’s presence, although the process of establishing security is a relative process and not absolute, given the absence of absolute security in all its aspects, no matter how far the state is. Of strength, industrial and military supremacy, and political stability, as weaknesses remain unclear in certain aspects that may be overlooked by those who try to implement security and whatever the security precautions of the state at home, or the state may face threats that may be unconventional or invisible such as unknown or terrorist forces as well. Today, Iraq faces transnational terrorist groups that enjoy international and regional support. They have been able to pose a threat to the interests of the state and its political entity. Therefore, such actions and others make national security exposed and endangered. Since 2003, the mindset of the decision-maker in Iraq tends to try to formulate the strategic construction of national security, and in the same context, what strengthens national security is that the entire national approach tries to find a security approach capable of dealing with the various internal and external challenges that affect Iraqi national security in particular. Those challenges whose impact and continuity are linked to external, regional and international projects